Asymmetric Difluoroboron Quinazolinone‐Pyridine Dyes with Large Stokes Shift: High Emission Efficiencies Both in Solution and in the Solid State. Issue 68 (9th November 2018) - Zhou, Jia; Liu, Lu; Pan, Ying; Zhu, Qiaoyu; Lu, Yajie; Wei, Jiacheng; Luo, Kang; Fu, Yang; Zhong, Cheng; Peng, Yiyuan; Song, Zhibin
Abstract: Boron difluoroquinazolinone‐pyridine (BODIQPy ) and substituted derivatives have been designed and synthesized. Strong emission with high fluorescence quantum yield both in solution (up to 0.99) and in solid state (up to 0.60) was achieved in these asymmetricBODIQPys . For 6‐halogen substitutedBODIQPys, the heavy atomic effect of bromine and iodine was suppressed in solution due to the strong electron‐withdrawing ability of theBODIQPy core. As a result, 6‐iodine substitutedBODIQPy shows the unusual fluorescence quantum yields (>0.70) in dichloromethane and tetrahydrofuran. In the solid state, the asymmetric structure induced a unique dimeric structure, and efficient luminescence was also observed. The formation of halogen bonds between carbonyl oxygen and bromine or iodine regulated the stacking mode and enhanced intermolecular interaction, resulting in a decline in the fluorescence quantum yield. In addition, a large Stokes shift was also achieved in these asymmetricBODIQPys . Abstract : Fluorescent dye : Asymmetric difluoroboron quinazolinone‐pyridine dyes (BODIQPys) were easily obtained through a two‐step reaction. These asymmetric BODIQPys exhibited high Stokes shift and strong emission with high fluorescence quantum yield both in solution (>0.99) and in the solid state (up to 0.60).